Analytical investigation of peristaltic nanofluid flow and heat transfer in an asymmetric wavy wall channel (Part II: Divergent channel). (November 2018) - Mosayebidorcheh, S.; Hatami, M.
Graphical abstract: Highlights: Two-phase peristaltic nanofluid flow in an divergent channel is modeled. Both upper and lower channel walls are considered in a wavy shape. Leaset Squae Method (LSM) is introduced as efficient analtical method for solution. The asymmetric shape effect of channel is investigated on the flow. Abstract: In this study, asymmetric peristaltic nanofluid flow in a two dimensional and divergent wavy channel is modeled and the heat transfer analysis is performed for it. The modeling is performed as two-phase model and it is assumed the magnetic field effects on the nanoparticles as magnetohydrodynamic (MHD) flow. Both upper and lower channel walls are considered in constant temperature and constant nanoparticle concentration. The governing equations were solved by analytical least square method (LSM) using the Maple 15.0 mathematical software and compared to available numerical results. The effect of some parameters existed in the equations (Geometry parameter, Brownian motion parameter, Dufour ( Du ) and Soret ( Sr ) numbers and etc.), are discussed on the velocities, temperature and nanoparticles concentration functions. As an important outcome, increasing in both Dufour ( Du ) and Soret ( Sr ) numbers lead to reduction in nanoparticles concentration while Dufour number increments make larger temperature profiles in the channel.